Análises morfológicas e bioacústicas em populações de Scinax hayii (Barbour, 1909) (Anura, Hylidae) ao longo da Mata Atlântica - Santos, Lucas Rodrigo dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims were to describe the morphometric, morphological and bioacoustic of Scinax hayii characters from the type locality and from three Operational Taxonomic Units to compare the localities with each other and registering founds variations at the characters analyzed. Were measured 18 morphometric characters in collected specimens on field and specimens provided of scientific collections. Morphological analysis was performed by the characters qualitative comparison and checking for the stripes and spots presence on the dorsal aspect. The bioacoustics analysis was performed with obtained recordings of recorded specimens in natural field conditions at all OTUs. Scinax hayii from Petrópolis has similar morphometric characters to OTU Serra do Mar. Specimens of OTU Planície Litorânea and Serra da Mantiqueira have smaller size (CRC: 34,2 - 41,5 mm; 31,5 - 42,2 mm; respectively). Scinax hayii from Petrópolis, Serra do Mar and Planície Litorânea are devoided stripes and spots on dorsal pattern. OTU Serra da Mantiqueira specimens differ from other locations by present dorsal coloration having stripes and spots. The S. hayii from Petrópolis vocalizations are shown like the OTU Serra do Mar call specimens. The recorded specimens vocalizations at OTUs Planície Litorânea and Serra da Mantiqueira differ from another locations and each other. Petrópolis and OTU Serra do Mar specimens by having similar morphological and bioacoustics characters indicate to be of the same species. The registered specimens at UTO Planície Litorânea have different morphological and bioacoustics characters from another locations, indicating that is a new specie. The UTO Serra da Mantiqueira specimens by having different morphological and bioacoustics characters from other locations indicate to be a new specie or the currently revalued specie as S. dolloi. In view of the morphological and bioacoustics analysis...

Os objetivos deste estudo foram descrever os caracteres morfométricos, morfológicos e bioacústicos de Scinax hayii da localidade tipo e de três Unidades taxonômicas operacionais (UTO) e comparar as localidades entre si registrando variações encontradas nos caracteres analisados. Foram mensurados 18 caracteres morfométricos em exemplares coletados em campo e exemplares de coleções científicas. A análise morfológica consistiu na comparação qualitativa de caracteres e verificação de presença de faixas e manchas em aspecto dorsal. A análise bioacústica foi realizada através de vocalizações obtidas de exemplares gravados em condições naturais de campo em todas as UTOs. Scinax hayii de Petrópolis apresenta caracteres morfométricos semelhantes a espécimes da UTO Serra do Mar. Os exemplares das UTOs Planície Litorânea e Serra da Mantiqueira apresentam menor tamanho corporal (CRC: 34,2 - 41,5 mm; 31,5 - 42,2 mm; respectivamente). Scinax hayii de Petrópolis, Serra do Mar e Planície Litorânea são desprovidos de faixas ou manchas em padrão dorsal. Exemplares da UTO Serra da Mantiqueira diferem das demais localidades por apresentar coloração dorsal possuindo faixas e manchas. As vocalizações de S. hayii de Petrópolis mostram-se semelhantes aos cantos de exemplares da UTO Serra do Mar. As vocalizações dos espécimes registrados nas UTOs Planície Litorânea e Serra da Mantiqueira diferem das demais localidades e entre si. Indivíduos de Petrópolis e UTO Serra do Mar por possuir caracteres morfológicos e bioacústicos semelhantes indicam ser a mesma espécie. Os exemplares registrados na UTO Planície litorânea possuem caracteres morfológicos e bioacústicos diferente das demais localidades, indicando ser uma nova espécie. Exemplares da UTO Serra da Mantiqueira por possuírem caracteres morfológicos e bioacústicos diferindo das demais localidades indicam ser uma nova...
Keywords: Ecologia animal; Animais; Biologia; Morfometria; Bioacustica; Anuro